Comparison of Ct PCI Score and Intraoperative PCI Score in Ovarian Cancer - Dr. Aishwarya Sharma; Dr. Aparna Khadelia, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Ovarian Cancer is the sixth most common cancer in the world2. Of all the gynecological malignancies, it is most lethal. Factors which can cause ovarian cancer are infertility, family history/genetic factors and previous hormone therapy. It has a poor prognosis because most of them are diagnosed in advanced stages. For ovarian cancer search for an ideal screening test has been going on. Transvaginal ultrasound, CA 125, and bimanual pelvic examination have been used in various screening studies to evaluate their role as screening tests but have not found much supportive evidence Aim and Objectives: 1.Comparison of CT PCI score and intraoperative PCI score in ovarian cancer.2. To know the extent of peritoneal disease in patients of ovarian cancer in north Indian population.3. To know the sensitivity and specificity of CT PCI score Methods: Study Design: Prospective study. Sample Size: 70 Results: Mean of Group CT PCI and Intraoperative PCI by unpaired t- test. Mean of group CT PCI were 9.3571with standard deviation of 6.64424 whereas mean of group Intraoperative PCI were 12.7857 with standard deviation of 10.73109. On descriptive analysis of CT PCI score the frequency percentage of LS 0 ( no tumor) was 4.3%, LS 1 ( upto 0.5 cm) was 0%, LS 2 ( upto 5cm) was 28.6% and LS 3( > 5cm) was 67.1%. On descriptive analysis of Intraoperative PCIscore the frequency percentage of LS 0 ( no tumor) was 7.1%, LS 1 ( upto 0.5 cm) was 2.9%, LS 2 ( upto 5cm) was 21.4% and LS 3( > 5cm) was 71.4%. histological type in ovarian cancer the frequency percentage of Papillary Adenocarcinoma was 14%, Adenocarcinoma was 8.5%, Serous Adenocarcinoma was 9.9%, Papillary Serous Carcinoma was 8.5% and majority of cases was found with Atypical Cells that is 59.1%. Conclusions: found that there is some discrepancy in CT PCI scores and surgical PCI score in individual regions because of which some of metastatic nodules are missed in CT PCI but can be seen intraoperatively.